2011
DOI: 10.1021/ja110190t
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Binding and Transport by Coenzyme Q

Abstract: Coenzyme Q10 (CoQ10) is one of the essential components of the mitochondrial electron-transport chain (ETC) with the primary function to transfer electrons along and protons across the inner mitochondrial membrane (IMM). The concomitant proton gradient across the IMM is essential for the process of oxidative phosphorylation and consequently ATP production. Cytochrome P450 (CYP450) monoxygenase enzymes are known to induce structural changes in a variety of compounds and are expressed in the IMM. However, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 60 publications
(100 reference statements)
4
88
1
Order By: Relevance
“…The actual structure of the ion-pair and the way in which TBA + is coupled to the UQ  anion radical is unclear and out of the scope of this report. However, the formation of UQ-Cation complexes has been reported before and it is therefore not unlikely that a similar process may occur in the described system [11].…”
Section: Effect Of Hydrophobic Quaternary Ammonium Salts In the Electsupporting
confidence: 80%
See 2 more Smart Citations
“…The actual structure of the ion-pair and the way in which TBA + is coupled to the UQ  anion radical is unclear and out of the scope of this report. However, the formation of UQ-Cation complexes has been reported before and it is therefore not unlikely that a similar process may occur in the described system [11].…”
Section: Effect Of Hydrophobic Quaternary Ammonium Salts In the Electsupporting
confidence: 80%
“…Other studies have suggested that UQ in the cell membrane may be involved in the function of sodium pumps in E. Coli and K. pneumoniae [7; 8], although this claim has been questioned [9; 10]. Recent reports have found that UQ may be involved in redox homeostasis and act as a regulator of calcium cations in mitochondria [11]. Furthermore, studies with membrane anchored quinones have shown that these molecules can drive the transfer of divalent cations (calcium, barium, strontium and magnesium) across biomimetic membranes [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the number of studies related to the chemical and redox features of CoQ family members has increased tremendously in the last three decades [8][9][10][11][12][13][14][15][16][17][18], many key features are still not well understood. In our last two publications we have shown that Coenzyme Q-1 (CoQ-1) and CoQ-10 undergo structural changes in strong alkaline environment or in the presence of Cytochrome P450 enzymes [19,20]. As main reaction products we identified several hydroxy derivatives of CoQ-1 and CoQ-10 [19,20].…”
Section: Introductionmentioning
confidence: 83%
“…In our last two publications we have shown that Coenzyme Q-1 (CoQ-1) and CoQ-10 undergo structural changes in strong alkaline environment or in the presence of Cytochrome P450 enzymes [19,20]. As main reaction products we identified several hydroxy derivatives of CoQ-1 and CoQ-10 [19,20]. The "isoprenoid Q and HQ" mainly function as electron and proton carriers [4][5][6][7], but it was not until recently that new properties of the hydroxy derivatives of CoQ-1 and CoQ-10 were unraveled highlighting their potential for binding earth-alkaline cations and even facilitating their transfer across biomimetic membranes [19,20].…”
Section: Introductionmentioning
confidence: 99%